Traditional newborn care practices in a tribal community of Tamilnadu, South India: A mixed methods study - Latha Arumugam; S Kamala; Kalaiselvan Ganapathy; Srikanth Srinivasan (Wolters Kluwer Medknow Publications, 2023)
Background and Objectives: Traditional newborn rearing practices play a vital role in neonatal morbidity and mortality. In this context, a concurrent mixed method study was conducted to identify the traditional practices in newborn care in tribal villages of Sittilingi Panchayat of Tamil Nadu, South India. Methods: The quantitative data were collected by a community-based cross-sectional study among 59 mothers of infants. Qualitative component included two focus group discussions (FGD) each with seven mothers and one traditional dai. Results: About 38.9% of newborns received colostrum, and 61.1% had prelacteal feeds. Majority (84.7%) of newborns had received appropriate thermal care. More than two-thirds (71.2%) of newborns were given bath before umbilical cord dropped off. During bathing, 83.1% were massaged and 67.8% had their vernix removed. Practice of blowing into nostrils (45.7%), substance application on the cord (94.9%), tepid sponging during fever (28.8%), sweet flag application over umbilicus for colic (8.5%), herbal medications during diarrhea (40.6%) and cold (25.4%), exposure to sunlight (67.8%) during jaundice, oil instillation in nostrils (76.3%), and ears (32.2%) to protect against infection were reported. Majority reported approaching traditional health practitioners during illness. Similar practices were reported in the FGDs. The beliefs related to these practices were explored. Conclusion: Both beneficial and harmful practices in newborn care were identified. Primary health care workers like ASHAs could be trained to recognize traditional newborn practices in their field areas to deliver appropriate behavior change communication to preserve safe practices and avoid harmful practices to improve newborn health.